2019
DOI: 10.1007/s13595-019-0865-4
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal adjustment of primary and secondary growth in maritime pine under simulated climatic changes

Abstract: & Key message Reducing irrigation by up to 75% in spring decreased primary and secondary growth in Pinus pinaster Aiton saplings, whereas an extra irrigation in September prompted secondary growth, confirming the high plasticity of xylogenesis in this species. & Context Water availability is the main limiting factor for plant growth and forest productivity in drought-prone environments, such as the Mediterranean region. Future scenarios for this region predict an increase in spring drought and in autumn precip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
(49 reference statements)
1
12
0
3
Order By: Relevance
“…It is an economically important species (e.g., pulp, wood, resin), representing about 2% of the Portuguese National Gross Domestic Product. In Portugal, the response of maritime pine to increased spring drought has already been studied under field (Vieira et al, 2017) and greenhouse conditions (Garcia-Forner et al, 2019;Vieira et al, 2019). The rain exclusion experiment carried out in the field revealed that the rate of cell production and tracheid differentiation was reduced by the simulated drought (Vieira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is an economically important species (e.g., pulp, wood, resin), representing about 2% of the Portuguese National Gross Domestic Product. In Portugal, the response of maritime pine to increased spring drought has already been studied under field (Vieira et al, 2017) and greenhouse conditions (Garcia-Forner et al, 2019;Vieira et al, 2019). The rain exclusion experiment carried out in the field revealed that the rate of cell production and tracheid differentiation was reduced by the simulated drought (Vieira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The identified negative convergent event years correspond to extreme drought years and were also detected in other studies analyzing extreme growth reduction in the Iberian Peninsula ( Gazol et al, 2018 ; Sánchez-Salguero et al, 2018 ). Low water availability limits tree growth directly by reducing the rate of cambial cell division ( Vieira et al, 2017b , 2019 , 2020 ) and indirectly by reducing photosynthesis and the soluble sugars available for secondary growth ( Cartenì et al, 2018 ). Low water availability associated with warmer temperatures can trigger stomatal closure ( Roman et al, 2015 ) in isohydric species such as P. pinaster ( Ripullone et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in temperature and precipitation regimes may increase drought risk, which can negatively affect trees’ physiological performance ( Garcia-Forner et al, 2019 ), carbon allocation ( Cartenì et al, 2018 ), and growth ( Vieira et al, 2019 ). In fact, changes in intensity, duration, and frequency of droughts are responsible for many observed shifts on vegetation and forest dieback ( DeSoto et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pinus pinaster is a gymnosperm species with a key environmental and forestry relevance into the northwestern Mediterranean area, where it is used for afforestation due to its fast growth, high phenotypic plasticity and stress tolerance, soil stabilization capacity and the quality of its timber and oleoresins [5,6]. Moreover, this species is also a good example of the climate-associated reductions in plant biomass yield related to regional climatic changes, increasing abiotic-heat and drought-and biotic stress pressure, which are also a main constraint for other Pinus species [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%